2011
DOI: 10.1021/jf200824c
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Accumulation and Expression of Anthocyanin Biosynthetic Genes in Radish (Raphanus sativus)

Abstract: Radish [Raphanus sativus (Rs)] is an important dietary vegetable in Asian countries, especially China, Japan, and Korea. To elucidate the molecular mechanisms of anthocyanin accumulation in radish, the gene expression of enzymes directly involved in anthocyanin biosynthesis was analyzed. These genes include phenylalanine ammonia lyase (PAL), cinnamate 4-hydroxylase (C4H), 4-coumarate-CoA ligase (4CL), chalcone synthase (CHS), chalcone isomerase (CHI), flavanone 3-hydroxylase (F3H), dihydroflavonol reductase (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
77
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 37 publications
8
77
1
Order By: Relevance
“…Radishes are cultivated to produce seed oil and sprouts, as well as edible taproots, which contain valuable phytochemicals such as glucosinolates and flavonoids (Blažević and Mastelić 2009;Park et al 2011). Some radish varieties have red skin and/or flesh due to anthocyanin accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Radishes are cultivated to produce seed oil and sprouts, as well as edible taproots, which contain valuable phytochemicals such as glucosinolates and flavonoids (Blažević and Mastelić 2009;Park et al 2011). Some radish varieties have red skin and/or flesh due to anthocyanin accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…LcMYB1 controls anthocyanin biosynthesis in litchi, and LcUFGT might be the structural gene that is targeted and regulated by LcMYB1 (Lai et al, 2014). Concerning the anthocyanin biosynthesis in radish, Park et al (2011) reported that RsDFR and RsANS were found to accumulate in the flesh or skin, and radish skin contained higher CHS, CHI, and F3H transcript levels than radish flesh. Lim et al (2015) isolated the RsMYB1 gene from red radish (red skin) plants and suggested that RsMYB1 is an actively positive regulator for anthocyanin biosynthesis in radish plants.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of F3'H in root skin and flesh was assayed by RT-qPCR assay using a 20 μL reaction mix containing 1 μL of 10X diluted cDNA templates, 10 μL of SYBR Premix Ex-Taq II (TaKaRa Bio), and 0.25 μM of 26S ribosomal RNA (26S) primer (Park et al, 2011; forward 5'-AACACCCTTTGTGGGTTCTAGGT-3' and reverse 5'-GCCCTCGACCTATTCTCAAACTT-3') and the above F3'H primers. Each RT-qPCR assay was conducted using a Thermal Cycler Dice Real-Time System (TaKaRa Bio) with an initial denaturation of 30 s at 95°C, followed by 50 cycles of denaturation for 5 s at 95°C, annealing for 10 s at 58°C (F3'H)/56°C (26S), and elongation for 20 s at 72°C.…”
Section: Expression Analysis Of Radish Anthocyanin Biosynthesis Genesmentioning
confidence: 99%
“…Radish anthocyanins are brightly colored over a wide pH range and their multiple acylation with hydroxycinnamic acids contributes to their remarkable heat stability in acidic environments (Jing et al, 2012). Radish anthocyanins have been widely used as natural colorants and ammonia lyase (PAL), cinnamate 4-hydroxylase (C4H), 4-coumarate-CoA ligase (4CL), CHS, CHI, F3H, DFR, and ANS, was investigated in white and red radishes (Park et al, 2011). However, little attention has been paid to the relationship between F3'H expression and root color in radishes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation